Landschaftsfotografie und Naturhermeneutik - Zur Ästhetik erlebter und dargestellter Natur - Falter, Reinhard; Hasse, Jürgen (ERDKUNDE, 2001)
The idea of landscape is very important in geography. In this article Landscape is understood from its totally impression. This view stands in opposite to reductionism, projectionism and constructivism. Photography is discussed according to its potentiality and limits of presentation. Pictures of the American photographer Richard Misrach are used to set an example. From these pictures of Richard Misrach, which seem to be absolutely unclassical, relationships to classical landscape are presented. Finally an idea of landscape is formulated, which is based on concepts from antiquity or the Far East. For that purpose the concept of atmospheres is referred to. This concept, developed by Hermann Schmitz, connects subject and object.